Correlation Between The Level Of Knowledge Of Young Women About Menstrual Disorders - Aisyah Lbs, Siti; Traine, Mega (Cattleya Darmaya Fortuna, 2023)
Menstrual disorders often occur in women of reproductive age due to the process of shedding of the uterine wall accompanied by bleeding that occurs repeatedly every month, except during pregnancy. The first day of menstruation is counted as the start of each menstrual cycle. Menstruation will occur in 3-7 days. At the beginning of the research, asking them about menstrual disorders, it was found that 9 students did not understand about menstrual disorders and 3 students knew about menstrual disorders. The aim of the research: to determine the relationship between the level of knowledge of young women about menstrual disorders in SMA Negeri 1 Panyabunan Selatan Class The instrument used was a questionnaire to obtain the data needed in the research using primary data collection techniques. The results of the analysis proved that the majority of respondents' level of knowledge was good knowledge as many as 6 people (20%) based on the results of statistical tests obtained data that the majority of knowledge was sufficient knowledge as many as 21 people (70%), while the minority is 3 people (10%) with less knowledge. The results of the research show that there is a relationship between knowledge based on age (p value = 0.11), knowledge based on information sources (p value = 0.000), and knowledge based on the environment (p value -0.000) of young women regarding menstrual disorders at SMA Negeri 1 Panyabungan Selatan Class XII, South Panyabungan District, Mandailing Natal Regency. The conclusion from the research results is that the level of knowledge of young women about menstrual disorders at SMA Negeri 1 Panyabungan Selatan is 6 people (20%) with good knowledge, 21 people (70%) with sufficient knowledge, the remaining minority is 3 people (10%) with poor knowledge.